The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1590/s0074-02761989000100013
|View full text |Cite
|
Sign up to set email alerts
|

Três novas espécies de tripanosomatídeos de insetos isolados em Alfenas, Minas Gerais, Brasil

Abstract: Três novas espécies de tripanosomatídeos foram isoladas em Alfenas, MG, Brasil: Herpetomonas anglusteri sp. n., do intestino posterior de Liopygia ruficorins (Diptera: Sarcophagidae); Crithidia roitmani sp. e.e Crithidia de souzai sp. n., do intestino médio e o posterior de Ornidia obesa (Diptera: Syrphidae). O isolamento foi feito em meio complexo de roitmanmas os três isolados cresceram bem no meio definido do mesmo Autor. Os clones foram obtidos em ágar-sangue de carneiro, desfibrinado, em placas de Petri, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…Furthermore, it demonstrates at the ultrastructural level that such forms are capable of dividing by binary fission. (Fiorini et al 1989). A cloned strain has been axenically maintained since then in Roitman's chemically defined medium (Roitman et al 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it demonstrates at the ultrastructural level that such forms are capable of dividing by binary fission. (Fiorini et al 1989). A cloned strain has been axenically maintained since then in Roitman's chemically defined medium (Roitman et al 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites H. roitmani was isolated from the¯y Ornidia obesa (Fiorini et al 1989) and has been maintained axenically in Roitman's chemically de®ned medium (Roitman et al 1972). Stock cultures were grown for 72 h at 28°C and then kept in a refrigerator (4°C) for 1±2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Since its isolation, H. roitmani has appeared to be quite a remarkable trypanosomatid: (a) it is a member of a restricted group of symbiont-bearing trypanosomatids, which includes Crithidia deanei (Carvalho 1973), C. desouzai (Fiorini et al 1989), C. oncopelti (Newton and Horne 1957), Blastocrithidia culicis (Novy et al 1907), and T. cobitis (Lewis and Ball 1980); (b) it was ®rst described as a member of the Crithidia genus, mainly due its morphology that closely resembles choanomastigotes (Fiorini et al 1989); (c) it was reclassi®ed as Herpetomonas (Faria-e-Silva et al 1991) based on the opisthomastigote forms and on isoenzymatic analysis; (d) opisthomastigotes of H. roitmani could be obtained in a high yield (98%) and it was shown that they can proliferate in culture, unlike other Herpetomonas species (Faria-e-Silva et al 1996); (e) recent studies (Teixeira et al 1997) suggest that H. roitmani may represent a new group of¯agellates, and it was suggested to use the term opisthomorph (OPM) to designate forms in which the kinetoplast is located posteriorly to the nucleus (as in opisthomastigotes) but have a body shape somewhat resembling choanomastigote forms. In view of these characteristics, we decided to analyze further the transformation process of promastigote (PRO) into OPM forms in H. roitmani, investigating the changes that occur on the surface-exposed carbohydrate residues and also in the surface anionic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of biochemical and molecular criteria confirmed misclassification of trypanosomatids in genera based exclusively on traditional criteria. This fact has been especially observed for species of Herpetomonas (Camargo et al 1992; Faria‐e‐Silva et al 1994; Fiorini et al 1989; Hollar, Lukes, and Maslov 1998; Jankevicius et al 1993; Nunes et al 1994; Roitman et al 1976; Teixeira et al 1996; Teixeira et al 1997).…”
mentioning
confidence: 86%